Impairment of invasion and maturation and decreased selectivity of Plasmodium falciparum in G6PD Viangchan and Mahidol variants - Palasuwan, D; Palasuwan, A; Boonpeng, K; Ketprasit, N; Imwong, M; Kulkeaw, K (Oxford University Press, 2021)
Background. Protection against Plasmodium falciparum is observed in a population deficient in glucose-6-phosphate dehydrogenase (G6PD), particularly in African and Mediterranean regions. However, such protection remains unknown among G6PD-deficient individuals in Southeast Asia.